The Effect of 15% Moringa Leaf Extract Gel on Gingival Wound Healing of Post-Curettage Wistar Rats With Type 2 Diabetes Mellitus Condition - Eka Pramudita Ramadhany; Valeo Adika Laksana; Ni Luh Desy Ayu Susilahati; Muhammad Rafif Musyaffa; Ni Wayan Ari Wulansari; Ni Putu Natasya Pretty Shinta Mahadewi; I Dewa Agung Ayu Indraswari Pramesti (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: Diabetes mellitus is one of the biggest global health emergencies in the 21st century and >90% of cases are type 2. Diabetes mellitus and periodontitis are related diseases. Patients with diabetes mellitus who exhibit early signs of periodontitis in their gingival tissue may benefit from periodontal interventions such as curettage and adjunctive therapeutic. Numerous studies show the antioxidant and anti-inflammatory effects of Moringa oleifera leaves decrease the levels of AGEs in individuals with hyperglycemia and promote unimpeded wound healing. The objective of this research is to determine the effect of 15% Moringa leaf extract gel on the healing of post-curettage Wistar rat gingival wounds with type 2 diabetes mellitus. Material and Method: Wistar rats were separated into two groups namely, CMC-Na and 15% gel Moringa leaf extract. Gracey curette is used on the rats periodontal pockets. Mice were euthanized and histological observations were carried out in three fields of view using image raster software with 100x magnification. Results and Discussion: The treatment group exhibited a higher mean level of gingival wound healing (Re-epithelialization and fibroblast cell) compared to the CMC-Na group. Mann-Whitney U test indicated significant disparity (p<0.05) between the two groups. The impact of flavonoids, saponins, and tannins found in Moringa leaf extract increase higher average off re-epithelialization and fibroblast cell. Conclusion: Moringa leaf extract gel 15% have effect of increasing gingival wound healing in wistar rats with Diabetes mellitus type 2 after curettage.